2020
DOI: 10.1002/gcc.22904
|View full text |Cite
|
Sign up to set email alerts
|

The orphan nuclear receptor NR0B2 could be a novel susceptibility locus associated with microsatellite‐stable, APC mutation‐negative early‐onset colorectal carcinomas with metabolic manifestation

Abstract: Colorectal cancer (CRC) is a high incidence cancer and major cause of cancer mortality. Though disease‐causing tumor suppressors for major syndromes are well characterized, about 10% of CRC is familial but without mutations in known tumor suppressors. We exhaustively screened 100 polyposis families for APC germline mutations and identified 13, which are APC mutation‐negative, microsatellite‐stable (MSS), and with undetectable mutation in known tumor suppressors. Whole exome sequencing in three probands uncover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…For instance, orphan nuclear receptor NR0B2 was found to be a novel susceptibility gene for the metabolic manifestation of early-onset CRC. 36 Moreover, a multiomics analysis revealed that the metabolites yielded significant interaction effects between early-onset and late-onset CRC patients. 37 Elevated uric acid is common in patients with obesity, diabetes, and hyperlipidemia or other metabolic syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, orphan nuclear receptor NR0B2 was found to be a novel susceptibility gene for the metabolic manifestation of early-onset CRC. 36 Moreover, a multiomics analysis revealed that the metabolites yielded significant interaction effects between early-onset and late-onset CRC patients. 37 Elevated uric acid is common in patients with obesity, diabetes, and hyperlipidemia or other metabolic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…When regarding this difference, the genomic alterations in early‐onset lesions could provide some explanations. For instance, orphan nuclear receptor NR0B2 was found to be a novel susceptibility gene for the metabolic manifestation of early‐onset CRC 36 . Moreover, a multiomics analysis revealed that the metabolites yielded significant interaction effects between early‐onset and late‐onset CRC patients 37 …”
Section: Discussionmentioning
confidence: 99%
“…Despite this, approximately 80–85% of EOCRCs are sporadic, microsatellite stable tumours 35 . Lam et al 36 . demonstrated a link between NR0B2 frameshift variants and increased susceptibility to microsatellite stable, APC‐negative EOCRC.…”
Section: Pathological Features and Molecular Profiles Of Eocrcmentioning
confidence: 99%
“…Despite this, approximately 80-85% of EOCRCs are sporadic, microsatellite stable tumours. 35 Lam et al 36 demonstrated a link between NR0B2 frameshift variants and increased susceptibility to microsatellite stable, APC-negative EOCRC. Further, recent molecular research has demonstrated a higher tumour mutational burden and distinct innate immune signature of EOCRC, has correlated specific gene mutations (SSA1, C7, CFD, CXCL3, IL1B, MET and TNS1), and aberrant pathways (wild-type WTN and mutated TGFβ pathway) with poorer overall survival (OS) in EOCRC and has identified accelerated ageing in normal mucosa of EOCRC patients as a potential contributor to carcinogenesis.…”
Section: Pathological Features and Molecular Profiles Of Eocrcmentioning
confidence: 99%
“…Methylation of MGMT and CALCA could be used as new molecular markers of prognosis in testicular germ cell tumors (TGCT) 27 . Furthermore, the orphan nuclear receptor NR0B2 may represent a new susceptibility locus associated with early-onset colorectal cancer 28 .…”
mentioning
confidence: 99%